A kinome‐wide screen using a NanoLuc LATS luminescent biosensor identifies ALK as a novel regulator of the Hippo pathway in tumorigenesis and immune evasion. Issue 11 (20th August 2019) - Nouri, Kazem; Azad, Taha; Lightbody, Elizabeth; Khanal, Prem; Nicol, Christopher J.; Yang, Xiaolong
Abstract : The Hippo pathway is an emerging signaling pathway that plays important roles in organ size control, tissue homeostasis, tumorigenesis, metastasis, drug resistance, and immune response. Although many regulators of the Hippo pathway have been reported, the extracellular stimuli and kinase regulators of the Hippo pathway remain largely unknown. To identify novel regulars of the Hippo pathway, in this study we created the first ultra‐bright NanoLuc biosensor (BS) to monitor the activity of large tumor suppressor (LATS) kinase 1, a central player of the Hippo pathway. We show that this NanoLuc BS achieves significantly advanced sensitivity and stability both in vitro using purified proteins and in vivo in living cells and mice. Using this BS, we perform the first kinome‐wide screen and identify many kinases regulating LATS and its effectors yes‐associated protein (YAP) and transcriptional co‐activator with PDZ‐ binding motif (TAZ). We also show for the first time that activation of receptor tyrosine kinase anaplastic lymphoma kinase (ALK) by its extracellular ligand family with sequence similarity (FAM)150 activates Hippo effector YAP/TAZ by increasing their nuclear translocation. Significantly, we show that constitutively active ALK induces tumorigenic phenotypes, such as increased cancer cell proliferation/colony formation via YAP/TAZ and elevated immune evasion via YAP/TAZ‐programmed death‐ligand 1 in breast and lung cancer cells. In summary, we have developed a new LATS BS for cancer biology and therapeutics research and uncovered a novel ALK‐LATS‐YAP/TAZ signaling axis that may play important roles in cancer and possibly other biologic processes.—Nouri, K., Azad, T., Lightbody, E., Khanal, P., Nicol, C. J., Yang, X. A kinome‐wide screen using a NanoLuc LATS luminescent biosensor identifies ALK as a novel regulator of the Hippo pathway in tumorigenesis and immune evasion. FASEB J. 33, 12487–12499 (2019). www.fasebj.org